Design optimization of linear permanent magnet generator for wave energy conversion - Memon, A.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents the optimization of linear permanent magnet generator for wave energy conversion. The finite element analysis has been carried out in order to determine the electromagnetic characteristics such as; air-gap flux density and induced-EMF. The copper loss and iron loss are evaluated individually and the effects of main leading dimension which have significant influence on the efficiency of linear permanent magnet generator are analyzed. The optimal values for the ratio of radially magnetized magnets to the pole pitch and outer radius of translator to outer radius of stator are identified, which results maximum efficiency. Â© 2015 IEEE.